Pengaruh Kecerdasan Numerik dan Penguasaan Konsep Matematika terhadap Kemampuan Berpikir Kritik Matematika - Ari Irawaan (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
The purpose of this study is to analyze and test hypotheses about the influence of numerical intelligence and mathematical concepts to the criticism athematical thinking skills. The hypothesis of this study include: 1) There is a direct nfluence on the ability to think intelligence numerical mathematics criticism. 2) There is a direct effect of mastery of mathematical concepts to the criticism athematical thinking skills. 3) There is a direct effect of the numerical intelligence mastery of mathematics concepts. 4) There is no direct effect of intelligence numerical mathematical thinking skills through mastery of critical math concepts. The method used in this study is a survey method. Affordable population is students of class VII school year 2012/2013 Junior High School in Depok Cimanggis. Sample size of 91 students, with the sampling technique used is random sampling, taken 3 public schools. Research instruments used were shaped PG numerical aptitude tests as much as 25 questions, test mastery of math concepts PG shaped by 20 questions, and thinking skills of mathematics in the form of criticism essay 10 questions, which has tested its validity. Data analysis using path analysis. Retrieved hypothesis testing results the following conclusions. The first hypothesis testing results show that: 1) there is a direct influence on the ability to think intelligence numerical mathematics criticism.; 2) there is a direct effect of mastery of mathematical concepts to the criticism mathematical thinking skills.; 3) there is a direct influence of the numerical intelligence mastery of mathematics concepts.; 4) there is no indirect effect wit criticism numerical mathematical thinking skills through mastery of mathematical concepts. Keywords: Intelligence numerical, mathematical concepts, critical thinking math